2015
DOI: 10.1007/s10086-015-1528-1
|View full text |Cite
|
Sign up to set email alerts
|

Thermography measurements and latent heat documentation of Norwegian spruce (Picea abies) exposed to dynamic indoor climate

Abstract: Hygroscopic materials hold the potential to reduce ventilation loads in a building by damping the peak fluctuations of the indoor relative humidity. Of particular interest is the moisture buffer capacity of wooden surfaces. This paper investigates, the response of Norwegian spruce (Picea abies) samples to changes of indoor relative humidity as well as the corresponding latent heat release during moisture buffering. A climate chamber was used to subject samples to dynamic air humidity. Thermographic techniques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…As may be seen, the surface temperature on the radial and tangential surfaces rises more rapidly (mean t max = 48 s), but reaches a lower maximum temperature (mean DT max of 1.4-1.5°C) than the transverse surface for which the rise is higher (mean DT max of 3.6°C) and takes longer to reach its peak value (mean t max = 282 s). The results of Kraniotis et al (2016) on the tangential surface of spruce heartwood are of the same order of magnitude as the current findings, albeit the behaviour was observed to be closer to that seen on the transverse surfaces of the specimens tested in this present work (t max = 500 s/DT max = 2.1°C). This difference is most probably attributable to the different experimental procedure adopted by Kraniotis and co-workers, who measured the surface temperature change on wood that had a nonzero initial moisture content and under conditions of slowly increasing relative humidity, changing from 25 to 90% over the course of 12 h. Further, the work of Kraniotis et al (2016) was on spruce heartwood, which would doubtlessly behave differently to the Scots pine used in this study that contained both sapwood and heartwood, whilst the specimens also differed in size which would have undoubtedly affected the mass and heat transfer characteristics.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…As may be seen, the surface temperature on the radial and tangential surfaces rises more rapidly (mean t max = 48 s), but reaches a lower maximum temperature (mean DT max of 1.4-1.5°C) than the transverse surface for which the rise is higher (mean DT max of 3.6°C) and takes longer to reach its peak value (mean t max = 282 s). The results of Kraniotis et al (2016) on the tangential surface of spruce heartwood are of the same order of magnitude as the current findings, albeit the behaviour was observed to be closer to that seen on the transverse surfaces of the specimens tested in this present work (t max = 500 s/DT max = 2.1°C). This difference is most probably attributable to the different experimental procedure adopted by Kraniotis and co-workers, who measured the surface temperature change on wood that had a nonzero initial moisture content and under conditions of slowly increasing relative humidity, changing from 25 to 90% over the course of 12 h. Further, the work of Kraniotis et al (2016) was on spruce heartwood, which would doubtlessly behave differently to the Scots pine used in this study that contained both sapwood and heartwood, whilst the specimens also differed in size which would have undoubtedly affected the mass and heat transfer characteristics.…”
Section: Discussionsupporting
confidence: 76%
“…Brueckner et al (2012), for example, investigated the surface temperature change during adsorption in untreated spruce wood panels, finding that a surface temperature increase of 2°C occurred when the ambient relative humidity (RH) rose from 20 to 90%. Recently, the question of whether this enthalpy change could be used to reduce the energy consumption of buildings, has become the subject of speculation and research (Kraniotis et al 2016). Nevertheless, for it to be correctly considered in building physics models, accurate data about the temperature changes in wood arising from sorption are required, and this forms the subject matter of the study reported herein.…”
Section: Introduction Background and Objectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moisture transfer between indoor air and hygroscopic materials also affects the indoor temperature because of the conversion of latent heat (Hameury 2005;Kraniotis et al 2016;Nore et al 2017). Due to the phase change that humidity undergoes during the process of moisture exchange between hygroscopic material and surrounding air, wood temperature increases when moisture is absorbed and decreases during drying (Simonson et al 2002;Hameury 2005;Kraniotis et al 2016). This leads to the possibility of reducing energy needed to heat, cool and ventilate buildings, especially in tandem with a well-controlled HVAC system (Osanyintola and Simonson 2006;Nore et al 2017).…”
Section: Latent Heat Exchangementioning
confidence: 99%